Early (<4 Weeks) Versus Standard (≥ 4 Weeks) Endoscopically Centered Step‐Up Interventions for Necrotizing Pancreatitis. (October 2018) - Trikudanathan, Guru; Tawfik, Pierre; Amateau, Stuart K.; Munigala, Satish; Arain, Mustafa; Attam, Rajeev; Beilman, Gregory; Flanagan, Siobhan; Freeman, Martin L.; Mallery, Shawn
Abstract : OBJECTIVES: Current guidelines for necrotizing pancreatitis (NP) recommend delay in drainage ± necrosectomy until 4 or more weeks after initial presentation to allow collections to wall off. However, evidence of infection with clinical deterioration despite maximum support may mandate earlier (<4 weeks) intervention. There are concerns, but scant data regarding risk of complications and outcomes with early endoscopic intervention. Our aim was to compare the results of an endoscopic centered step‐up approach to NP when initiated before versus 4 or more weeks. METHODS: All patients undergoing intervention for NP were managed using an endoscopically centered stepup approach, with transluminal drainage whenever feasible, ±necrosectomy, and/or percutaneous catheter drainage as needed, with surgery only for failures. Interventions were categorized as early or standard based on timing of intervention (<4 weeks or ≥ 4 weeks from onset of pancreatitis). Demographic data, indications and timing for interventions, number and type of intervention, mortality and morbidity (length of stay in hospital and ICU) and complications were compared. RESULTS: Of 305 patients with collections associated with NP, 193 (63%) (median age‐52 years) required intervention, performed by a step‐up approach. Of the 193 patients, 76 patients underwent early and 117 patients standard intervention. 144 (75%) interventions included endoscopic drainage ± necrosectomy. As compared with standard intervention, early intervention was more often performed for infection (91% vs. 39%, p < 0.05), more associated with acute kidney injury (43% vs. 32%, p = 0.09), respiratory failure (41% vs. 22%, p = 0.005), and shock (13% vs. 4%, p < 0.05). Organ failure improved significantly after intervention in both groups. There was a significant difference in mortality (13% vs. 4%, p = 0.02) and need for rescue open necrosectomy (7% vs. 1%, p = 0.03) between groups. Patients undergoing early intervention had increased median hospital (37 days vs. 26 days, p = 0.01) and ICU stay (median 2.5 days vs. 0 days, p = 0.001). There was no difference in complications. CONCLUSIONS: When using an endoscopically centered step‐up strategy in necrotizing pancreatitis, early (<4 weeks) interventions were more often performed for infection and organ failure, with no increase in complications, similar improvement in organ failure, slightly increased need for surgery, and relatively low mortality. Early endoscopic drainage ± necrosectomy should be considered when there is a strong indication for intervention.